Trotabresib (CC-90010) in combination with adjuvant temozolomide or concomitant temozolomide plus radiotherapy in patients with newly diagnosed glioblastoma. Issue 1 (28th October 2022) - Vieito, Maria; Simonelli, Matteo; de Vos, Filip; Moreno, Victor; Geurts, Marjolein; Lorenzi, Elena; Macchini, Marina; van den Bent, Martin J; Del Conte, Gianluca; de Jonge, Maja; Martín-Soberón, Maria Cruz; Amoroso, Barbara; et al.
Abstract: Background: Standard-of-care treatment for newly diagnosed glioblastoma (ndGBM), consisting of surgery followed by radiotherapy (RT) and temozolomide (TMZ), has improved outcomes compared with RT alone; however, prognosis remains poor. Trotabresib, a novel bromodomain and extraterminal inhibitor, has demonstrated antitumor activity in patients with high-grade gliomas. Methods: In this phase Ib, dose-escalation study (NCT04324840), we investigated trotabresib 15, 30, and 45 mg combined with TMZ in the adjuvant setting and trotabresib 15 and 30 mg combined with TMZ+RT in the concomitant setting in patients with ndGBM. Primary endpoints were to determine safety, tolerability, maximum tolerated dose, and/or recommended phase II dose (RP2D) of trotabresib. Secondary endpoints were assessment of preliminary efficacy and pharmacokinetics. Pharmacodynamics were investigated as an exploratory endpoint. Results: The adjuvant and concomitant cohorts enrolled 18 and 14 patients, respectively. Trotabresib in combination with TMZ or TMZ+RT was well tolerated; most treatment-related adverse events were mild or moderate. Trotabresib pharmacokinetics and pharmacodynamics in both settings were consistent with previous data for trotabresib monotherapy. The RP2D of trotabresib was selected as 30 mg 4 days on/24 days off in both settings. At last follow-up, 5 (28%) and 6 (43%) patients remain on treatment in the adjuvant and concomitant settings, respectively, with 1 patient in the adjuvant cohort achieving complete response. Conclusions: Trotabresib combined with TMZ in the adjuvant setting and with TMZ+RT in the concomitant setting was safe and well tolerated in patients with ndGBM, with encouraging treatment durations. Trotabresib 30 mg was established as the RP2D in both settings.